Métamorphoses et permanences des parcours professionnels en France (1968-2018) - Marion Plault (Revue de la Régulation)
The issue of this thesis is to question the idea of a contemporary time which would be described as a “deep dislocation of the wage earners” and which would result in a major transformation of the professional paths from a generation of workers to another. The empirical foundations this “dominant narrative” are examined on the basis of three dimensions of the professional paths: employment, unemployment, job insecurity and qualification. The professional paths of three cohorts of workers (1945, 1960 and 1975) are compared one to each other on the basis of INSEE’s Labour Force surveys and on Échantillon Démographique Permanent datas. This thesis’ general hypothesis challenges the idea of an opposition between the professional paths of, in one hand, generations of the “full-employment” whom had entered their jobs during the 1970’ and on the other hand the later generations, whose careers are said to be marked by a general deterioration of their working conditions.